Voice Search Paradigm Shift in Content Searching in Libraries – A Study - V, Jeevitha; E. S., Kavitha (International Journal of Information Studies, 2025)
This paper evaluates and analyses the features and drawbacks of various major searching methodologies deployed in libraries. This paper also provides an in-depth analysis of the difficulties encountered by the users in effectively using them and the resultant fallouts arising out of the complexities of their usage. This paper introduces Voice based searching solutions as the enhanced and viable alternative to the existing systems addressing all the constraints of the current search methodologies enabled applications for in build the current system.